Observation of weak anti-localization and electron-electron interaction on few-layer 1T′-MoTe2 thin films - Wang, Qin (2020)
Electronic transports of few-layer 1T'-MoTe2 films are measured at temperatures down to 0.26 K. The lowtemperature conductivity exhibits logarithmic temperature dependence and negative magneto response. The negative magnetoconductivity can be well fitted by the two-dimensional weak anti-localization theory taking a single channel of electrons into account, with the parameters α ≈ -0.5 and lφ ∝ T-0.5. The logarithmic temperature dependence has a positive slope κ ≈ 0.75, indicating the dominance of electron-electron interaction over the weak anti-localization effect, with an apparently negative Coulomb screening factor F that demands future work for clarification.